Effectiveness of creativity training and its relation to selected personality factors - Kabanoff, Boris [Verfasser]; Bottger, Preston [Verfasser] (My University, 1991)
"This exploratory study assesses the effectiveness of the Creative Problem Solving Program (Parnes, Noller and Biondi, 1977) for increasing the ideational fluency, flexibility and originality of trainees in a Master of Business Administration program. Pre- and post-training performances of trainess (N = 32) on the Torrance Tests of Creative Thinking (verbal) are compared with a control group of MBA students (N = 44). Compared to the control group, trainees demonstrate significant gains in originality. While both groups show an improvement in fluency." (author's abstract) ((en)) Im Rahmen einer explorativen Studie wird die Effektivität eines kreativen Problemlösungsprogramms bei Studenten einer Wirtschaftsverwaltungsschule untersucht. Bewertet werden insbesondere die Auswirkungen auf den Ideenfluss, die Flexibilität und Originalität der Trainees. In die Analyse werden auch verschiedene Persönlichkeitsfaktoren, wie z.B. Leistungsbereitschaft, Streben nach Einfluss und Annahme von Ideen einbezogen. (IAB)
Effektivität des Kreativitätstrainings und Beziehungen zu ausgewählten Persönlichkeitsfaktoren
Keywords: P 1.7 Benachteiligte; S 2.1.2 Berufsbildungsförderungsgesetz (BerBiFG); S 6.4 Dienstleistungsberufe; L 2.3.2 Handlungs- & problemorientierte Methoden; Kreativität; Förderung; Wirtschaftswissenschaftler; Problemlösen; Entscheidungsfindung; Leistungsmotivation; Persönlichkeitsmerkmal; Handlungsspielraum; Quantitative Angaben